Development and characterization of circRNA sponges to functionally inhibit miR-122 - Jost, Isabelle; Justus Liebig University Giessen (My University, 2017)
Recent advances in RNA sequencing (RNA-seq) techniques and sequence analysis methods have led to the discovery of thousands of exonic circular RNAs (circRNAs), expressed in many species. These covalently closed RNA circles were assumed to be alternative products of pre mRNA processing by the spliceosome. Being investigated more extensively only during the last five years, few circRNA candidates were characterized, and the understanding of their global biological relevance is still very limited. The currently best investigated circRNA is CDR1as/ciRS 7, which contains more than 70 miR-7 binding sites. It is thought to function as a microRNA (miRNA) sponge by competing for miR 7 binding with its targets. Due to their elevated stability compared with linear RNAs, circRNAs are particularly attractive for biotechnological and therapeutic applications. In order to experimentally substantiate the hypothesis that circRNAs are processed by the spliceosome, plasmid-encoded circRNA splicing reporters (minigenes) were generated. Sequence elements of the natural gene context were gradually removed and a detailed mutational analysis of splice signals was performed. The minigene derivatives were then transfected into cells and processing products were detected via RT-PCR. With this approach, the requirement of fundamental splicing signals for efficient and precise exon circularization was demonstrated. The results provide valid evidence for the involvement of the spliceosome in circRNA biogenesis.The very abundant and liver-specific miR-122 is an essential host factor in hepatitis C virus (HCV) infection. Miravirsen, which sequesters miR 122, is the first locked nucleic acid (LNA)-modified antisense oligonucleotide (oligo) drug for HCV treatment that has entered clinical trials. Based on the concept of the natural CDR1as/ciRS-7 miRNA sponge, artificial circRNA sponges for functional sequestration of miR-122 from HCV RNA were designed. The artificial circRNAs were synthesized in vitro by enzyme-based transcription and ligation of eight consecutive binding sites, followed by gel purification of the circular miRNA sponges. The in vitro generated circRNAs were transfected into cells and analyzed with respect to their subcellular distribution and their stability. Functional inhibition of miR-122 by the circRNAs sponges was tested in three different HCV reporter systems. Efficacy of the miR-122 circRNA sponges was analyzed in comparison to an unspecific circRNA, to their linear counterparts, as well as to miravirsen. The designed circRNA sponges clearly and specifically caused HCV-adverse effects in all tested reporter systems, which is evidence for the functional sequestration of miR 122. This demonstrates the potential of circRNAs to extend the spectrum of RNA therapeutics as pharmaceutical products in the future.

Dank der die jüngsten Fortschritte bei RNA Sequenziermethoden und der Analyse von Sequenzierungsdaten wurden Tausende von exonischen zirkulären RNAs (circRNAs) in vielen Spezies entdeckt. Es wird angenommen, dass diese kovalent geschlossenen RNA-Zirkel alternative Produkte der mRNA Prozessierung durch das Spleißosom darstellen. Da sie erst seit den letzten fünf Jahren eingehender untersucht werden, wurden bisher nur wenige circRNA Kandidaten funktionell charakterisiert, und das Verständnis für ihre übergreifende biologische Relevanz ist begrenzt. Die derzeit am besten untersuchte circRNA ist CDR1as/ciRS-7, die mehr als 70 miR-7 Bindestellen enthält. Es wird vermutet, dass CDR1as/ciRS-7 wie ein mikroRNA (miRNA) Schwamm wirkt, also um die Bindung von miR-7 mit den Ziel mRNAs konkurriert. circRNAs sind, durch ihre erhöhte Stabilität verglichen mit linearen RNAs, besonders attraktiv für biotechnologische und medizinische Anwendungsgebiete.Um die Hypothese, dass circRNAs vom Spleißosom generiert werden, experimentell zu untermauern, wurden Plasmide mit circRNA Spleiß-Reportern (Minigen-Konstrukte) hergestellt. Zuerst wurden Sequenzelemente aus dem Kontext des natürlichen Gens schrittweise entfernt, um dann eine detaillierte Mutationsanalyse der Spleißsignale durchzuführen. Die Minigen-Konstrukte wurden in Zellen eingebracht, und die Prozessierungsprodukte wurden mittels RT PCR analysiert. Mit Hilfe dieser Vorgehensweise konnte gezeigt werden, dass die grundlegenden Spleißsignale für die effiziente und präzise Zirkularisierung von Exons notwendig sind. Diese Ergebnisse liefern stichhaltige Beweise für die Beteiligung des Spleißosoms bei der Biogenese von circRNAs.Die sehr abundante und leber-spezifische miR-122 spielt bei der Infektion mit dem Hepatitis-C Virus (HCV) eine essentielle Rolle als Wirtsfaktor. Miravirsen sequestriert miR-122 und wurde als erstes LNA-modifiziertes Antisense-Oligonukleotid zur Behandlung von HCV in klinischen Studien geprüft. Basierend auf dem Konzept von CDR1as/ciRS-7 als miRNA Schwamm, wurden artifizielle circRNAs konzipiert und hergestellt, um miR-122 zu blockieren und dadurch HCV zu hemmen. Die Synthese von artifiziellen circRNAs erfolgte durch enzym-basierte Transkription und Ligation von acht aufeinanderfolgenden Bindestellen, gefolgt von einer Gel-Aufreinigung. Die circRNAs wurden dann transfiziert, um sie hinsichtlich ihrer Lokalisierung und Stabilität innerhalb der Zelle zu untersuchen. Die funktionelle Inaktivierung von miR-122 durch die circRNAs wurde mit drei verschiedenen HCV Reporter Systemen getestet. Dabei wurde die Wirksamkeit der zirkulären miRNA Schwämme, mit einer unspezifischen circRNA, dem jeweiligen linearen Gegenstück und miravirsen verglichen. Die circRNA Schwämme haben deutliche und spezifische HCV-hemmende Effekte, was ein Indiz dafür ist, dass miR-122 erfolgreich inaktiviert wurde. Dadurch konnte gezeigt werden, dass circRNAs das Potenzial haben als pharmazeutisches Produkt zukünftig zur Erweiterung des Spektrums von RNA Therapeutika beizutragen.
Entwicklung und Charakterisierung von circRNAs zur Inhibierung von miR-122
Keywords: circRNA1; zirkuläre RNA2; HCV3; Hepatitis C Virus4; ceRNA5; circRNA1; circular RNA2; HCV3; Hepatitis C Virus4; ceRNA5; ddc:570